Lentzea sokolovensis sp. nov., Lentzea kristufekii sp. nov. and Lentzea miocenica sp. nov., rare actinobacteria from Miocene lacustrine sediment of the Sokolov Coal Basin, Czech Republic - Lara, Ana Catalina; Kotrbová, Lucie; Keller, Moritz; Nouioui, Imen; Neumann-Schaal, Meina; Mast, Yvonne; Chroňáková, Alica (International journal of systematic and evolutionary microbiology, 2024)
The taxonomic position of three actinobacterial strains, BCCO 10_0061T, BCCO 10_0798T, and BCCO 10_0856T, recovered from bare soil in the Sokolov Coal Basin, Czech Republic, was established using a polyphasic approach. The multilocus sequence analysis based on 100 single-copy genes positioned BCCO 10_0061T in the same cluster as Lentzea waywayandensis, strain BCCO 10_0798T in the same cluster as Lentzea flaviverrucosa, Lentzea californiensis, Lentzea violacea, and Lentzea albidocapillata, and strain BCCO 10_0856T clustered together with Lentzea kentuckyensis and Lentzea alba. Morphological and chemotaxonomic characteristics of these strains support their assignment to the genus Lentzea. In all three strains, MK-9(H4) accounted for more than 80 % of the isoprenoid quinone. The diagnostic diamino acid in the cell-wall peptidoglycan was meso-diaminopimelic acid. The whole-cell sugars were rhamnose, ribose, mannose, glucose, and galactose. The major fatty acids (>10 %) were iso-C15 : 0, anteiso-C15 : 0, iso-C16 : 0, and C16 : 0. The polar lipids were diphosphatidylglycerol, methyl-phosphatidylethanolamine, phosphatidylethanolamine, hydroxy-phosphatidylethanolamine, phosphatidylglycerol, and phosphatidylinositol. The genomic DNA G+C content of strains (mol%) was 68.8 for BCCO 10_0061T, 69.2 for BCCO 10_0798T, and 68.5 for BCCO 10_0856T. The combination of digital DNA-DNA hybridization results, average nucleotide identity values and phenotypic characteristics of BCCO 10_0061T, BCCO 10_0798T, and BCCO 10_0856T distinguishes them from their closely related strains. Bioinformatic analysis of the genome sequences of the strains revealed several biosynthetic gene clusters (BGCs) with identities >50 % to already known clusters, including BGCs for geosmin, coelichelin, ε-poly-l-lysine, and erythromycin-like BGCs. Most of the identified BGCs showed low similarity to known BGCs (<50 %) suggesting their genetic potential for the biosynthesis of novel secondary metabolites. Based on the above results, each strain represents a novel species of the genus Lentzea, for which we propose the name Lentzea sokolovensis sp. nov. for BCCO 10_0061T (=DSM 116175T), Lentzea kristufekii sp. nov. for BCCO 10_0798T (=DSM 116176T), and Lentzea miocenica sp. nov. for BCCO 10_0856T (=DSM 116177T).
Keywords: zastoupení bazí; RNA ribozomální 16S; Bacterial Typing Techniques; Bacteria; DNA bakterií; fosfatidylethanolaminy; RNA, Ribosomal, 16S; techniky typizace bakterií; uhlí; fylogeneze; Česká republika; DNA, Bacterial; mastné kyseliny; Sequence Analysis, DNA; sekvenční analýza DNA; Base Composition; Czech Republic; Fatty Acids; Coal; Phylogeny; Actinobacteria; Actinomycetales; Phosphatidylethanolamines